Financial and digital financial literacy through social media use towards financial inclusion among batik small enterprises in Indonesia - Al-Shami, Samer Ali Hussein; Damayanti, Ratna; Adil, Hayder; Farhi, Faycal; Al Mamun, Abdullah (Elsevier Ltd, 2024)
Batik, an Indonesian textile art form, holds immense economic and cultural importance. Small and medium enterprises (SMEs) specialising in batik play a crucial role in Indonesia's economic growth and cultural preservation, contributing significantly to the gross domestic product (GDP) and preserving the nation's heritage. Nevertheless, these enterprises face several challenges, such as slow growth and limited access to credit. The batik industry also lags in financial literacy and the adoption of digital marketing strategies, hindering its development. This quantitative study aims to investigate the relationship between financial literacy, digital financial literacy, and financial inclusion in batik SMEs and also examined the moderating effect of online social networks. A survey was conducted involving 535 managers, owners, and financial officers of small batik enterprises. Subsequently, the SmartPLS statistical analysis method was employed for data analysis. The results demonstrate that financial literacy and digital financial literacy play a significant role in accessing financial inclusion for batik small enterprises. Moreover, the utilisation of social media was found to moderate these relationships, amplifying the impact of financial and digital literacy on financial inclusion. The findings contribute to the existing knowledge, provide insights for enhancing batik small enterprises, and propose a digital financial model to promote financial inclusion.